The Qur’anic Copying Tradition in Borneo: A Rasm Analysis of Abdul Hamid’s Giant Qur’an Manuscript - Luqman Abdul Jabbar; Ihsan Nurmansyah; Marsih Muhammad (Studia Quranika, 2026)
The existence of Quran manuscripts in Borneo has attracted  particular attention  in the history of Quranic transcription dissemination in the archipelago. This article delves into the history of Quran manuscripts in Borneo and the orthographic characteristics of their transcriptions. The methods employed include philological scholarship to examine the construction of the transcription process and codicology methods to uncover the manuscript's history. This article provides new insights into the map of Quran manuscript history in the archipelago. The Quran manuscripts in Borneo exhibit a more inclusive character in their transcription process. The application of the rasm usmani imla’i during the post-independence spread of printed Quran versions offers new knowledge about the treasure trove of Quranic transcriptions.